IMPROVING TAX ADMINISTRATION THROUGH ELECTRONIC TAX SYSTEMS AND THEIR ECONOMIC EFFICIENCY - Turayev Alijon Akmalovich,; Ilamonov Mexroj Akbar o‘g‘li, (TADQIQOTLAR, 2026)
Abstract.  The  digital  transformation  of  tax  administration  has  become  a  key reform  strategy  for  improving  revenue  collection,  reducing  compliance  costs,  and combating tax evasion. Based on data from the OECD, IMF, and case studies from Estonia, Rwanda, Brazil, and Uzbekistan, this study shows that electronic filing, e-payment,  and  integrated tax systems  help  reduce  the  tax  gap,  lower  administrative costs,  and  enhance  taxpayer  compliance.  The  article  concludes  with  policy recommendations to further improve the effectiveness of electronic tax systems and maximize their economic benefits.